2022
DOI: 10.3390/nu14132658
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Food Allergy Syndrome in Allergic March

Abstract: The association between pollen food allergy syndrome (PFAS) and allergic march remains unclear. In this prospective cohort study of the general population in Tokyo (T-Child Study), we found that sensitization to Cry j 1 and Fel d 1 at ages 5 and 9 years was associated with an increased risk of PFAS at 13 years old (at 5 years, Cry j 1: adjusted odds ratio aOR, 2.74; 95% confidence interval CI, 1.53–4.91; Fel d 1: aOR, 2.61; 95% CI, 1.31–5.19; at 9 years, Cry j 1: adjusted odds ratio aOR, 4.28; 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…We hypothesize that the severity of PFAS symptoms correlates with the concentration of birch pollen in the air, with these symptoms aggravating during the pollen season and shortly afterward [10]. In an article by Yasudo et al, it is proposed that PFAS could potentially be a part of the allergic march [17]. The study found that at the age of five, IgE sensitization to Bet v1 was observed in 2.2% of participants, and this percentage increased to 13.9% by the age of nine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We hypothesize that the severity of PFAS symptoms correlates with the concentration of birch pollen in the air, with these symptoms aggravating during the pollen season and shortly afterward [10]. In an article by Yasudo et al, it is proposed that PFAS could potentially be a part of the allergic march [17]. The study found that at the age of five, IgE sensitization to Bet v1 was observed in 2.2% of participants, and this percentage increased to 13.9% by the age of nine.…”
Section: Discussionmentioning
confidence: 97%
“…This increase in IgE level was identified as a risk factor for PFAS in adolescence. It is plausible that the boy is experiencing this phenomenon, progressing from pollinosis to a unique systemic reaction, as a manifestation of PFAS [17]. The patient reports allergy symptoms to peaches and plums, for which he has no sIgE detected.…”
Section: Discussionmentioning
confidence: 99%
“…PFAS/OAS can present in childhood, adolescence, or adulthood with prevalence rates ranging from 4.7 to over 20% in children and from 13 to 58% in adults, suggesting increased development over a lifetime and that PFAS/OAS may often be persistent [ 92 ]. Yasudo et al found that childhood symptoms of wheeze, eczema, or allergic rhinitis at age 5 or 9 were risk factors for the development of PFAS/OAS by age 13 years [ 93 ].…”
Section: Adolescencementioning
confidence: 99%